Maldives : Public Financial Management; Performance Report. (IMF Staff Country Reports; Country Report, 2010)
This paper focuses on the Public Financial Management-Performance Report for the Maldives. In line with the Public Expenditure and Financial Accountability (PEFA) methodology, the assessment focuses on the fiscal performance during 2005-08, and the institutions and procedures that were in place during this period. The assessment indicates that budget credibility of Maldives is weak. When corrected for concessional, external financing, aggregate expenditure estimates are reasonably accurate. However, there are significant variations in the allocation of expenditures by ministry, and actual revenues fell well below estimates in each year except 2006.